PROXIMATE PROPERTY AND THERMAL STABILITY CHARACTERIZATION OF CHEMICALLY ACTIVATED CARBON FOR ORGANIC FRICTION LINING MATERIALS (Nigerian Journal of Technology, 2024)
This work studied the proximate property and thermal stability of chemically activated carbon developed from agrowaste materials for organic friction linings. The proximate property, degradation steps, optimum degradation temperature (ODT) and oxidative stability (oxidation onset temperature (OOT) and oxidation temperature (OT)) characterizations were performed on two processed samples. Coconut shell activated carbon (CSAC) and palm kernel shell activated carbon (PKSAC) were used to prepared three compositions (%vol.) and particle sizes (µm); 0% CSAC : 100% PKSAC, 50% CSAC : 50% PKSAC, and 100% CSAC : 0% PKSAC and 60, 105 and 150 µm. Thermogravimetric analysis (TGA) and modulated differential scanning calorimetry (MDSC) methods were used to perform the characterizations and results compared with two commercial brakepads (CB1 and CB2) as controls.  The proximate analysis showed that 60µm of 0% CSAC : 100% PKSAC had the best results with 6.04% moisture, 3.99% volatile matter, 84.8% fixed carbon and 4.79% ash and compared well with the commercial friction lining materials (CB1: 2.27% moisture, 2.18% volatile matter, 45.47% fixed carbon, 48.86% ash; CB2: 1.92% moisture, 1.49% volatile matter, 37.21% fixed carbon, 58.07% ash). The thermal stability of 0% CSAC : 100% PKSAC, 50% CSAC : 50% PKSAC and 100% CSAC : 0% PKSAC samples with 150µm particle size showed percentage ODT increase of 18.3% and 15.8%; 37.1% and 34.2%; 17.8% and 15.3% when compared with CB1 and CB2 respectively. For all developed activated carbon compositions and particle sizes, the oxidation onset temperature (OOT) compared well with CB2 while oxidation temperature (OT) compared well with CB1. Overall, the developed activated carbon compositions showed suitability for organic friction lining applications.